MORPHOFUNCTIONAL STATE OF THE RATS’ EPIPHYSIS UNDER CONDITIONS OF HEAVY METAL SALTS INTOXICATION AND CORRECTION WITH MELATONIN - Pshychenko, V.V.; Cherno, V.S.; Chebotar, L.D.; Larycheva, O.M.; Petrova, O.I. (World of Medicine and Biology, 2024)
The study presents the data of morphological research of the rats’ pineal glands with heavy metal salt intoxication and correction of changes with melatonin. It was established that intoxication with salts of heavy metals leads to a morphological restructuring of the parenchyma and an imbalance in the processes of synthesis and secretion of the pineal gland’s metabolites. Morphological changes are expressed by a decrease in the total number of pinealocytes, swelling of the parenchyma, and the appearance of cysts, which indicates the development of hydropic dystrophy, cell necrosis and suppression of the functional activity of the pineal gland. The protective effect of exogenous melatonin consisted in reducing signs of oedema, the number of cysts, and their mean area, increasing the number of cells, changing morphometric indices and bringing them closer to the control indices. Melatonin is a potentially useful agent for neutralizing the toxic effects of heavy metal salts on the pineal gland.
Keywords: rats; pineal gland; heavy metals; melatonin; dystrophy; necrosis